Production Management of Dried Rajang Seasonings in the SME Paon D Jimbar Mesari Group in Bakbakan Village - I Ketut Selamet; I Ketut Darma; Kadek Putra Santika Narayana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Food Processing Program in Bakbakan Village, particularly conducted by the SME Paon D Jimbar Mesari group, aims to enhance community self-reliance and well-being through the packaging of durable Balinese traditional seasoning (genep spice) suitable for a shelf life of 1-2 years. The focus is on product development with an extended shelf life, allowing consumers to carry and use these seasonings conveniently while traveling. This program encompasses training in the utilization of appropriate technology to improve production, skills in the drying process, also production and marketing management. Consequently, the program has the potential to expand the market and sustainably increase the production of the SME Paon D Jimbar Mesari group.